Examination of the methodology of extension to support the competitiveness of the rural area - Kozári, József (Studia Mundi – Economica, 2018)
Discovering solutions tailored to local characteristics, tailored to personal and rural communities, as well as access to up-to-date knowledge is essential to ensure long-term security of the countryside. In Szilágyi-Boldizsár's view, recognizing all dimensions of rural security as well as interacting with one another as a dynamic unit, has a new type of approach, sense of responsibility and economic opportunity. (Szilágyi-Boldizsár, 2016) In this spirit, the article seeks to analyze the methods of knowledge transfer that can be applied with great efficiency in rural advisory services, thus ensuring dissemination of knowledge to promote the competitiveness of rural areas. The research focuses on analyzing decision-making processes and innovations that provide competitiveness, as well as discussing the practice of applying knowledge-based methods in detail.